The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ep.12923
|View full text |Cite
|
Sign up to set email alerts
|

Different parameters affecting the condensation rate on an active solar still—A review

Abstract: Passive solar stills are used for solar distillation. But the yield of passive still is very low, and often fails to meet the demand. Water is one of the fundamental sources for the survival of mankind on the globe. As world having just a little measure of water assets for utilization purpose, individuals living in undeveloped countries and urban zones are getting affected by consuming dirty water that prompts water‐borne illness. Despite the fact that groundwater is accessible in little amount, it must be sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…After reaching the boiling point of water, the water evaporates and it condenses on the solar still condenser cover. The various techniques employed in solar still, to raise the temperature of water and hence increases the productivity was studied from the detailed literatures reviews of Ravishankar et al [11], Kabeel et al [12] and Manokar et al [13][14][15]. From the detailed literature studies it is clear that water temperature can be improved by either feeding waste warm water or pre heat the water by incorporating the different solar collectors or concentrators.…”
Section: Introductionmentioning
confidence: 99%
“…After reaching the boiling point of water, the water evaporates and it condenses on the solar still condenser cover. The various techniques employed in solar still, to raise the temperature of water and hence increases the productivity was studied from the detailed literatures reviews of Ravishankar et al [11], Kabeel et al [12] and Manokar et al [13][14][15]. From the detailed literature studies it is clear that water temperature can be improved by either feeding waste warm water or pre heat the water by incorporating the different solar collectors or concentrators.…”
Section: Introductionmentioning
confidence: 99%
“…Rabhi confirmed that the use of an external condenser in order to reduce some humid air located in the evaporator, gives a clear growth in water production . The effectiveness can be enhanced by 47% when the external condenser is used . In this context; El‐Bahi added an outside condenser to a single‐basin type solar still with a minimum angle of inclination of 4°.…”
Section: Introductionmentioning
confidence: 87%
“…Climate change or seasonal changes directly affect productivity, which has been proven by studies and real‐life experiments . Other studies were based on improving the productivity of the single slope by several simple and cheap methods . Several theoretical and experimental studies in the literature show that the geometric shape itself of the distiller also influences efficiency .…”
Section: Introductionmentioning
confidence: 99%